Delighting the Customers' Senses - Key to Store Differentiation - Siraj, Sadaf; Kumari, Shyama (Indian Journal of Marketing, 2010)
The world of retail merchandising has come a long way since the days when general stores, that stocked everything from groceries to stationery, and small shops that sold limited varieties of products, reigned supreme. There is a movement now from the unorganized to the organized sector. There are now more modern retail formats such as supermarkets and malls. The whole concept of shopping has altered in terms of format and consumer buying behavior, ushering in a revolution in shopping in India.